Preparation method and application of material for removing heavy metals in lithium battery waste liquid
By combining chitosan with L-cysteine to form Cys-CTS material and using it in conjunction with CTAB and PAM, the problem of poor treatment of heavy metals in lithium battery waste liquid is solved, and a high-efficiency, low-cost and environmentally friendly heavy metal removal effect is achieved.
Patent Information
- Application Number
- CN202411791218.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is poor in treating high concentrations of heavy metals in lithium battery waste liquid, and flocculation agents may cause secondary pollution, resulting in poor water quality stability.
By combining chitosan with L-cysteine, a Cys-CTS material is formed and used in conjunction with cetyl trimethylammonium bromide (CTAB) and flocculant polyacrylamide (PAM), the efficient removal of heavy metals in lithium battery waste liquid is achieved.
This method significantly improves the removal efficiency of heavy metals, reduces treatment costs, simplifies the operation process, reduces the risk of secondary pollution, and maintains the stability of water quality for a long time.
Smart Images

Figure CN119660930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater treatment, and in particular to a material preparation method and application for removing heavy metals in lithium battery waste liquid. Background Art
[0002] At present, in the production of lithium batteries, the polluted wastewater produced contains a large amount of heavy metal ions and toxic and hazardous substances, such as chromium, cadmium, lead, etc. Chromium is one of the most toxic heavy metals. According to the drinking water guidelines formulated by the World Health Organization, the maximum allowable limit of total chromium is 0.05 mg / L. When present in higher concentrations, chromium can cause major health problems, especially Cr (VI), which is 500 times more toxic, mutagenic and carcinogenic than Cr (III). Heavy metals are bioaccumulative and will directly threaten human health after entering the food chain. In addition, the self-purification capacity of water bodies is limited, and heavy metal pollution that has accumulated in water bodies is difficult to completely remove. How to scientifically monitor and effectively remove heavy metal pollution in water bodies to a safe level is still a huge challenge facing environmental workers. Therefore, it is crucial to develop new, efficient and low-cost heavy metal removal technologies.
[0003] In recent years, modified adsorbents based on natural polymer materials have attracted extensive attention due to their environmental friendliness, renewability and high adsorption performance. Chitosan, as a natural polysaccharide material, has abundant amino and hydroxyl functional groups and has been widely used in wastewater treatment. However, the adsorption capacity and selectivity of chitosan are limited and often need to be improved through chemical modification methods such as graft copolymerization, cross-linking and acylation. L-cysteine, as a sulfur-containing amino acid, has a reducing and chelating property, making it an ideal candidate for binding to heavy metal ions.
[0004] At present, the commonly used heavy metal wastewater treatment technologies include chemical precipitation, ion exchange, membrane separation, and adsorption. However, these traditional heavy metal wastewater treatment technologies have some significant disadvantages, such as high treatment costs, relatively complex operation procedures, limited adaptability to heavy metal ions, frequent replacement of treatment materials, and poor stability of treated water quality. Flocculation precipitation can avoid these disadvantages and is easier to operate. It is usually relatively low-cost, and only needs to add suitable flocculants through a simple precipitation process to achieve effective treatment of heavy metals; it has good treatment effects on a variety of heavy metal ions and strong adaptability; and after treatment, it can keep the water quality stable for a long time. It is a more practical and advantageous method for treating heavy metal wastewater. However, the existing flocculation precipitation method still has disadvantages such as poor treatment effect on high-concentration wastewater, large sludge production, and secondary pollution caused by flocculants. Summary of the invention
[0005] In order to solve the above technical problems existing in the prior art, the embodiment of the present invention provides a material preparation method and application for removing heavy metals in lithium battery waste liquid. The technical solution is as follows:
[0006] A method for preparing a material for removing heavy metals from lithium battery waste liquid, the method comprising:
[0007] S11, dispersing chitosan (CTS) in acetic acid solution to form a uniform solution;
[0008] S12, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC), N-hydroxysuccinimide (NHS) and L-cysteine (L-Cys) to the uniform solution obtained in step S11 in order to obtain a mixed solution;
[0009] S13, adjusting the pH value of the mixed solution obtained in step S12, then sealing, and continuously stirring the mixed solution in a light-proof condition for 24 hours;
[0010] S14, adding anhydrous ethanol to the stirred solution obtained in step S13 to precipitate the product, then centrifugally separating the precipitate, and washing the precipitate after centrifugation with ethanol and deionized water, and vacuum drying the obtained sample at 50° C. to obtain the material Cys-CTS.
[0011] In the step S11, the concentration of the acetic acid solution is 1 Vol%, and the ratio of chitosan to the acetic acid solution is 1 g: 50-300 ml.
[0012] In the step S11, the deacetylation degree of CTS exceeds 95%, and the viscosity is 100-200 map·s.
[0013] In step S12, the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and L-cysteine is 3:2.3:4:3;
[0014] The purity of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 95%, the purity of the N-hydroxysuccinimide is 98%, and the purity of the L-cysteine is 99%.
[0015] In the step S12, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is replaced by a carbodiimide reagent, and N-hydroxysuccinimide is replaced by sulfo-N-hydroxysuccinimide.
[0016] In step S13, the pH value of the mixed solution is adjusted to 1-3.5; the pH is generally adjusted using a hydrochloric acid solution containing 2% by volume of concentrated hydrochloric acid.
[0017] The stirring rate in step S13 is 400-700 rpm.
[0018] The speed of the centrifuge for centrifugation separation of the precipitate in step S14 is above 500 rpm.
[0019] The amount of anhydrous ethanol used in step S14 is 4-6 times that of the acetic acid solution (1 Vol%).
[0020] In step S14, ethanol and deionized water are used for washing three or more times respectively.
[0021] The application of the above-mentioned material for removing heavy metals from lithium battery waste liquid includes the following steps:
[0022] S21, adjusting the pH value of the lithium battery waste liquid, adding cetyltrimethylammonium bromide (CTAB) and the material Cys-CTS obtained in step S14 to the lithium battery waste liquid, and performing magnetic stirring to obtain a mixed stirring liquid;
[0023] S22, adding polyacrylamide as a flocculant to the mixed solution obtained in step S21, stirring for 30 minutes, allowing the mixture to settle for 24 hours, and filtering to remove heavy metals in the solution.
[0024] In step S21, the lithium battery waste liquid contains Cr(VI), and the concentration of Cr(VI) is 30 mg / L.
[0025] In step S21, the pH of the lithium battery waste liquid is adjusted to 1-4, generally using hydrochloric acid solution or sodium hydroxide solution.
[0026] In step S21, the purity of cetyltrimethylammonium bromide (CTAB) is 99%, the dosage is 300-600 mg / L, and the dosage of Cys-CTS is 2-5 g / L.
[0027] In step S21, the hexadecyltrimethylammonium bromide is replaced by dodecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.
[0028] The magnetic stirring rate in step S21 is 400-700 rpm and the time is 2 h.
[0029] In the step S22, the mass fraction of the flocculant PAM is 0.1%, and the amount of the flocculant is 25-150 ml / L.
[0030] The PAM is non-ionic and has a molecular weight of 5 million.
[0031] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:
[0032] The above scheme has a simple process. The CTS used in the process has the characteristics of being widely available, abundant, non-toxic, and easily degradable. It has low cost and very good environmental and economic benefits. The addition of flocculants is conducive to subsequent precipitation and separation, and is not prone to secondary pollution. The reagents used are all common drugs that can be purchased on the market. They are low-cost, highly operable, economically efficient, and can be mass-produced.
[0033] In the above scheme, the synergistic effect of Cys-CTS and CTAB combined with the use of PAM significantly improved the removal efficiency of heavy metals. This combined process provides a powerful solution for the efficient removal of heavy metals through the synergistic effect of chemical and physical mechanisms.
[0034] The above scheme adopts a one-step precipitation process and uses flocculant PAM to precipitate and remove heavy metal complexes. The operation process is simple and convenient for large-scale treatment of heavy metal-containing wastewater such as lithium battery waste liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 It is an FT-IR graph of CTS and Cys-CTS involved in a material preparation method for removing Cr(VI) from lithium battery waste liquid provided by an embodiment of the present invention;
[0037] Figure 2 1 is a SEM-EDS image of CTS and Cys-CTS involved in the embodiments of the present invention;
[0038] Figure 3 is the Cr(VI) removal rate of CTS and Cys-CTS without adding CTAB in the embodiment of the present invention;
[0039] Figure 4 This is the effect of the Cys-CTS dosage on the Cr(VI) removal rate under the condition of adding CTAB in the embodiment of the present invention.
[0040] Figure 5 The effect of Cys-CTS and CTAB on the removal rate of Cr(VI) in the embodiment of the present invention;
[0041] Figure 6 The effect of the pH of the Cr(VI)-containing solution on the Cr(VI) removal rate during the experiment in the embodiment of the present invention;
[0042] Figure 7It is the effect of the amount of PAM added on the precipitation effect in the embodiment of the present invention;
[0043] Figure 8 It is the influence of the precipitation time on the precipitation effect in the embodiment of the present invention. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0045] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0046] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0047] The embodiment of the present invention provides a material preparation method and application for removing heavy metals in lithium battery waste liquid.
[0048] A method for preparing a material for removing heavy metals from lithium battery waste liquid, comprising:
[0049] S11, dispersing chitosan in the acetic acid solution to form a uniform solution;
[0050] S12, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and L-cysteine in order to the uniform solution obtained in step S11 to obtain a mixed solution;
[0051] S13, adjusting the pH value of the mixed solution obtained in step S12, then sealing, and continuously stirring the mixed solution in a light-proof condition for 24 hours;
[0052] S14, adding anhydrous ethanol to the stirred solution obtained in step S13 to precipitate the product, then centrifuging, and washing the precipitate after centrifugation with ethanol and deionized water, and vacuum drying the obtained sample at 50° C. to obtain the material Cys-CTS.
[0053] The application of the material for removing heavy metals in lithium battery waste liquid comprises the following steps:
[0054] S21, adjusting the pH value of the lithium battery waste liquid, adding hexadecyltrimethylammonium bromide and the material Cys-CTS obtained in step S14 to the lithium battery waste liquid, and performing magnetic stirring to obtain a mixed stirring liquid;
[0055] S22, adding polyacrylamide as a flocculant to the mixed solution obtained in step S21, stirring for 30 minutes, allowing the mixture to settle for 24 hours, and filtering to remove heavy metals in the solution.
[0056] This will be described below with reference to specific embodiments.
[0057] Example 1
[0058] 0.1379 g of potassium dichromate was dissolved in ultrapure water to prepare a 30 mg / L Cr(VI) solution to simulate actual Cr(VI) waste liquid.
[0059] Take 200ml of the prepared Cr(VI) solution in a conical flask, adjust the solution to pH=3, add 0.4g Cys-CTS, and stir magnetically for two hours. Then add 10ml of 0.1% PAM to the mixed solution, stir thoroughly for 30min, and let it settle naturally for 24h. After precipitation, sample and filter to detect the concentration of Cr(VI) in the solution. The concentration of Cr(VI) was analyzed by 1,5-diphenylcarbohydrazide spectrophotometry.
[0060] The above Cys-CTS samples were characterized by Figure 1 The characteristic peaks and Figure 2 The SEM images and EDS element mapping can prove that L-Cys was successfully inserted into CTS.
[0061] The Cys-CTS in Example 1 was replaced by CTS, and the other conditions in Example 1 were not changed, and the Figure 3 . Figure 3 is the Cr(VI) removal rate of CTS and Cys-CTS without adding CTAB. Figure 3 It can be seen that the introduction of L-Cys enhanced the selective adsorption capacity of CTS for Cr(VI), and increased the Cr(VI) removal rate from 23.2% to 74.1%.
[0062] Example 2
[0063] 0.1379 g of potassium dichromate was dissolved in ultrapure water to prepare a 30 mg / L Cr(VI) solution to simulate actual Cr(VI) waste liquid.
[0064] Take 200ml of the prepared Cr(VI) solution in a conical flask, adjust the solution to pH=3, add 0.4g Cys-CTS and 0.06g CTAB, and stir magnetically for two hours. Then add 10ml of 0.1% PAM to the mixed solution, stir thoroughly for 30min, and then let it settle for 24h. After precipitation, sample and filter to detect the concentration of Cr(VI) in the solution. The concentration of Cr(VI) was analyzed by 1,5-diphenylcarbohydrazide spectrophotometry.
[0065] The dosage of Cys-CTS in Example 2 was changed to 0.1 g, 0.2 g, 0.6 g, 0.8 g, and 1.0 g, respectively. The other conditions in Example 2 were not changed, and the obtained Figure 4 . Figure 4 The effect of Cys-CTS dosage on Cr(VI) removal efficiency under the condition of adding CTAB. Figure 4 It can be seen that the dosage of Cys-CTS has a significant effect on the efficiency of Cr(VI) removal. As the dosage increases from 0.1g to 1.0g, the removal rate increases from about 88% to nearly 96%. This phenomenon shows that the introduction of L-Cys enhances the removal ability of CTS and provides more complexation sites to capture Cr(VI).
[0066] The addition of Cys-CTS in Example 2 was changed to only add CTAB. The other conditions of Example 2 were not changed. Combined with Example 1, it can be obtained that Figure 5 . Figure 5 The effect of Cys-CTS and CTAB on the removal rate of Cr(VI) is shown in Figure 2. Figure 5 It can be seen that the effect of adding Cys-CTS or CTAB alone is not good. When Cys-CTS is used in combination with CTAB, the removal efficiency is significantly improved from 74.1% to 94.82% through the synergistic effect of chemical and physical mechanisms.
[0067] The pH of the solution in Example 2 was changed to pH=1, pH=2, pH=4, pH=6, pH=8, pH=10, and pH=12, respectively. The other conditions of Example 2 were not changed, and the results were: Figure 6 . Figure 6 Effect of solution pH on Cr(VI) removal rate during the experiment. Figure 6 It can be seen that the Cr(VI) removal rate under acidic conditions is much higher than that under alkaline conditions.
[0068] Example 3
[0069] 0.1379 g of potassium dichromate was dissolved in ultrapure water to prepare a 30 mg / L Cr(VI) solution to simulate actual Cr(VI) waste liquid.
[0070] Take 200ml of the prepared Cr(VI) solution in a conical flask, adjust the solution to pH=3, add 0.6g Cys-CTS and 0.06g CTAB, and stir magnetically for 2h. Then add 10ml of 0.1% PAM to the mixed solution, stir thoroughly for 30min, and let it settle naturally for 24h. After precipitation, take the supernatant and test the turbidity of the supernatant.
[0071] The dosage of PAM in Example 3 was changed to 0ml, 5ml, 15ml, 20ml, and 30ml respectively. The other conditions of Example 3 were not changed, and the result was Figure 7 . Figure 7 The effect of PAM dosage on precipitation effect. Figure 7 It can be seen that with the increase in the amount of PAM added, the turbidity of the solution dropped rapidly from about 375 NTU in the 0-10 mL stage, indicating that the introduction of PAM effectively promoted the aggregation and sedimentation of particles. As the amount of PAM added continued to increase (10-30 mL), the turbidity change tended to be stable and slightly decreased. This shows that after exceeding a certain amount, the additional addition of PAM no longer significantly improves the turbidity.
[0072] The precipitation time after adding PAM in Example 3 was changed to 1 h, 4 h, 8 h, 12 h, 16 h and 20 h respectively. The other conditions of Example 3 were not changed, and the results were as follows: Figure 8 . Figure 8 The effect of precipitation time on precipitation effect. Figure 8 It can be seen that with the increase of sedimentation time, the turbidity of the solution tends to decrease, and the suspended particles are gradually and effectively removed. After 12 hours, the turbidity of the solution decreases slowly and tends to be stable at 24 hours.
[0073] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a material for removing heavy metals from lithium battery waste liquid, characterized in that: The method comprises: S11, dispersing chitosan in the acetic acid solution to form a uniform solution; S12, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and L-cysteine in order to the uniform solution obtained in step S11 to obtain a mixed solution; S13, adjusting the pH value of the mixed solution obtained in step S12, then sealing, and continuously stirring the mixed solution in a light-proof condition for 24 hours; S14, adding anhydrous ethanol to the stirred solution obtained in step S13 to precipitate the product, then centrifugally separating the precipitate, and washing the precipitate after centrifugation with ethanol and deionized water, and vacuum drying the obtained sample at 50° C. to obtain the material Cys-CTS.
2. The method for preparing a material for removing heavy metals from lithium battery waste liquid according to claim 1, characterized in that: In the step S11, the concentration of the acetic acid solution is 1 Vol%, and the ratio of chitosan to the acetic acid solution is 1 g: 50-300 ml.
3. The method for preparing a material for removing heavy metals from lithium battery waste liquid according to claim 1, characterized in that: In step S12, the mass ratio of chitosan, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and L-cysteine is 3:2.3:4:3; The purity of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is 95%, the purity of the N-hydroxysuccinimide is 98%, and the purity of the L-cysteine is 99%.
4. The method for preparing a material for removing heavy metals from lithium battery waste liquid according to claim 1, characterized in that: In the step S12, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide is replaced by a carbodiimide reagent, and N-hydroxysuccinimide is replaced by sulfo-N-hydroxysuccinimide.
5. The method for preparing a material for removing heavy metals from lithium battery waste liquid according to claim 1, characterized in that: In step S13, the pH value of the mixed solution is adjusted to 1-3.
5.
6. The use of the material for removing heavy metals in lithium battery waste liquid according to claim 1, characterized in that: The steps include: S21, adjusting the pH value of the lithium battery waste liquid, adding hexadecyltrimethylammonium bromide and the material Cys-CTS obtained in step S14 to the lithium battery waste liquid, and performing magnetic stirring to obtain a mixed stirring liquid; S22, adding polyacrylamide as a flocculant to the mixed solution obtained in step S21, stirring for 30 minutes, allowing the mixture to settle for 24 hours, and filtering to remove heavy metals in the solution.
7. The use of the material for removing heavy metals in lithium battery waste liquid according to claim 6, characterized in that: In step S21, the pH of the lithium battery waste liquid is adjusted to 1-4.
8. The use of the material for removing heavy metals in lithium battery waste liquid according to claim 6, characterized in that: In step S21, the dosage of hexadecyltrimethylammonium bromide is 300-600 mg / L, and the dosage of Cys-CTS is 2-5 g / L.
9. The use of the material for removing heavy metals in lithium battery waste liquid according to claim 6, characterized in that: In step S21, the hexadecyltrimethylammonium bromide is replaced by dodecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride.
10. The use of the material for removing heavy metals in lithium battery waste liquid according to claim 6, characterized in that: In the step S22, the mass fraction of the flocculant PAM is 0.1%, and the amount of the flocculant is 25-150 ml / L.
Citation Information
Patent Citations
Method for preparing heavy metal ion adsorbent by using floc produced by flocculation
CN115121229A
Cited By
Carbon source for sewage treatment as well as preparation method and application thereof
CN121020820A